Efektifitas Penggunaan Strategi Index Card Match (Icm) Dan Strategi Snowball Throwing (St) Pada Mata Pelajaran Ilmu Pengetahuan Sosial ( Ips ) Terpadu Pada Materi Keadaan Alam Di Indonesia Kelas Vii Smp Negeri 3 Sawit Boyolali - Nastiti, Winda; , Dr. Tjipto Subadi, M.Si (2016)
This research was conducted at SMPN 3 Sawit. The purpose of this study is assess and describing the differences in the effectiveness of Index Card Match (ICM) with Snowball Throwing (ST) in learning the material state of Nature in Indonesia. This research uses descriptive quantitative methods of experimental . Oil Research conducted 6 months that is between the months of August 2015 to January 2016. The population in this study were all students of class VII SMP N 3 Sawit 2015/2016 school year, divided VIIF of class VII and class G. the sample in this study is 33 students. Results on the aspects of knowledge using research instruments in the form of pre-test and post-test totaling 15 items. The average value of class VII E as the control classes showed the results of pre-test a maximum score of 14, the minimum score 5 and the average value of 10:09, while for the post test the maximum score is 15, the minimum score is 8 and the average value of 11.75 and class VII F as an experimental class of the pre test results obtained with a maximum value of 15 minimum value of 7 and an average value of 11.21 was post test results show a high of 15 and the lowest value of 11, while the average value shows 14.45. the results of the average value of the experimental class increased after getting treatment in learning is implementing the strategy of Snowball Throwing (ST).